2018
DOI: 10.3390/nano8110903
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Amorphous and Crystalline State of Multinary Alloy Nanoparticles in An Ionic Liquid

Abstract: Controlling the amorphous or crystalline state of multinary Cr-Mn-Fe-Co-Ni alloy nanoparticles with sizes in the range between ~1.7 nm and ~4.8 nm is achieved using three processing routes. Direct current sputtering from an alloy target in the ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide leads to amorphous nanoparticles as observed by high-resolution transmission electron microscopy. Crystalline nanoparticles can be achieved in situ in a transmission electron microscope by exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
0
31
0
1
Order By: Relevance
“…To obtain crystalline NPs, their group used three processing routes including 1) in situ electron beam irradiation in a TEM, 2) ex situ heating in vacuum, and 3) using a high-power impulse magnetron sputtering (HiPIMS) procedure. [34] They found that the crystal structure of CrMnFeCoNi HEA-NPs varied with different processing methods. For example, a body-centered cubic (BCC) structure is formed during in situ electron beam crystallization, whereas longer ex situ annealing induces a face-centered cubic (FCC) structure.…”
Section: Physical Vapor Deposition Methodsmentioning
confidence: 99%
“…To obtain crystalline NPs, their group used three processing routes including 1) in situ electron beam irradiation in a TEM, 2) ex situ heating in vacuum, and 3) using a high-power impulse magnetron sputtering (HiPIMS) procedure. [34] They found that the crystal structure of CrMnFeCoNi HEA-NPs varied with different processing methods. For example, a body-centered cubic (BCC) structure is formed during in situ electron beam crystallization, whereas longer ex situ annealing induces a face-centered cubic (FCC) structure.…”
Section: Physical Vapor Deposition Methodsmentioning
confidence: 99%
“…When sample areas with a large amount of amorphous material were investigated in the TEM, crystalline NPs were spontaneously formed under the electron beam. 82 In order to promote the crystallization of the NPs outside of the TEM, the Fe/Al@[OPy] [NTf 2 ] sample was heated (annealed) for altogether 10 h at 100 C in vacuum (see ESI for analyses of intermediate annealing times with Fig. S24 and S25 †).…”
Section: Top-down Approachmentioning
confidence: 99%
“…The second approach yielded in ultrasmall CoCrFeMnNi NPs with diameters ranging from 2 to 4 nm with either amorphous or crystalline structure depending on the experimental parameters. 18 By sputtering material from a nearly equimolar HEA target into an ionic liquid, NPs can be synthesized instead of lms usually obtained by the method. However, the required ionic liquid and the complexity of the method strongly limit its applicability.…”
Section: Introductionmentioning
confidence: 99%